PENGARUH PENERAPAN LAYANAN BIMBINGAN KLASIKAL DAN NON KLASIKAL DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMP NEGERI 4 NABIRE - Jator Tandian; Ujang Rohman; Atiqoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the implementation of classical and non-classical guidance services and learning motivation on student achievement at SMP Negeri 4 Nabire. The method used in this study is a quantitative approach with an experimental design. The instruments used to collect data are a learning motivation questionnaire and a student achievement test. Data collection was carried out by distributing questionnaires to students and administering a learning achievement test after the implementation of guidance services. The data obtained were then analyzed using the SPSS 27 program with a two-way ANOVA analysis technique. The results showed that the guidance service method, both classical and non-classical, had a significant effect on student achievement, with a very high F value (165.743) and a very low p-value (0.000). In addition, learning motivation was also found to have a significant effect on student achievement, with an F value of 99.719 and a p-value of 0.000. These findings indicate that learning motivation is a key factor in student academic achievement. The study also found a significant effect of the interaction between guidance methods and learning motivation on student achievement. Students with high learning motivation benefit more from classical tutoring methods, while students with lower motivation benefit more from more flexible non-classical tutoring methods. Based on these results, it is recommended that schools introduce and implement tutoring methods that are appropriate to students' characteristics and learning motivation, in order to improve their academic achievement. A more personalized approach in tutoring services and efforts to improve students' learning motivation will have a positive impact on academic achievement.